Primary Small Bowel Amelanotic Melanoma and Intestinal Intussusception: A Case Report - Machado Guimbala , Vitor; Kormann, Raul Francisco; Neto, Plínio Cézar; Vicentini Karvat, João Gabriel; Neto, Ricardo Pasquini; Pruner Vieira, João Victor; Figueroa Magalhães, Maria Cristina (Brazilian Journal of Case Reports, 2023)
Primary gastrointestinal melanomas (PGM) are usually asymptomatic in the early stages, leading to misdiagnosis. We reported the case of a 75-year-old male patient admitted to our service due to hematochezia, and fatigue. Primary investigation showed small bowel intussusception and surgical treatment was performed. Histopathology and immunohistochemistry analysis identified primary small bowel amelanotic melanoma at an advanced tumor stage. Whereas the patient had a sudden impairment of performance status during hospitalization, no curative oncological approach could be performed. This report highlights the clinical and imaging findings that led to the primary gastrointestinal amelanotic melanoma diagnosis in an elderly patient with intestinal intussusception. The early recognition of prior intussusception signs in adults and elder patients may lead to an earlier oncological diagnosis and a better prognosis.